Test of animal feed made from coffee skin, tofu dreg and head of catfish on broilers - Andrew Setiawan Rusdianto; Andi Eko Wiyono; Noer Indah Maulida Putri; Oryzatania Windaru Runteka (Universitas Darussalam Gontor, 2020)
Waste is one of the problems that can cause pollution to the environment. Utilization of waste as chicken feed is an efficient way of fulfilling chicken nutrition, has high economic value and can reduce environmental pollution. One of the optimal waste that is a waste of coffee skin, tofu pulp and catfish head. The nutritional content of artificial feed accordance with SNI 8173.3.3: 2015 concerning broiler chicken feed, which has a moisture content of 7.68%, 9.95% ash, 8.82% fat, 22,91% protein, 0.8% calcium and 53.99% carbohydrates. The purpose of this study was to determine the effect of artificial feeding on feed consumption, daily weight gain, and feed conversion. This study used a completely randomized design. The results showed that of the five treatments with different formulations there was the best treatment, namely treatment P2 with the formulation of 50% artificial feed : 50% commercial feed produced an average daily weight gain of 93.4 g, feed consumption of 2310.5 g and feed conversion as much as1.24 g. If the value of high feed consumption is followed by high weight gain, the feed conversion rate decreasing so that the ration can be said to be efficient in generating daily weight gain.